Total skin electron beam therapy as palliative treatment for cutaneous manifestations of advanced, therapy-refractory cutaneous lymphoma and leukemia - Hauswald, Henrik; Zwicker, Felix; Rochet, Nathalie; Uhl, Matthias; Hensley, Frank W.; Debus, Jürgen; Herfarth, Klaus; Bischof, Marc (Radiation oncology, 2012)
Background: To retrospectively access the outcome and toxicity of a total skin electron beam therapy (TSEBT) in patients with cutaneous lymphoma (CL) or leukemia. Patients and methods: Treatment results of 25 patients (median age 63 years; 5 female, 20 male) with cutaneous manifestations of advanced and therapy-refractory CL (n = 21; T-cell lymphomas n = 18, B-cell lymphomas n = 3) stage IIB-IV or leukemia (n = 4; AML n = 2, CLL n = 1, PDC n = 1) treated between 1993 and 2010 were reviewed. All patients were symptomatic. The median total dose was 29Gy, applied in 29 fractions of median 1 Gy each. Results: The median follow-up was 10 months. Palliation was achieved in 23 patients (92%). A clinical complete response was documented in 13 (52%) and a partial response in 10 patients (40%). The median time to skin progression was 5 months (range 1-18 months) and the actuarial one-year progression-free survival 35%. The median overall survival (OS) after the initiation of TSEBT was 10 months (range 1-46 months) and the actuarial one-year OS 45%. TSEBT related acute adverse events (grade 1 or 2) were observed in all patients during the treatment period. An acute grade 3 epitheliolysis developed in eight patients (32%). Long-term adverse events as a hyperpigmentation of the skin (grade 1 or 2) were documented in 19 patients (76%), and a hypohidrosis in seven patients (28%). Conclusion: For palliation of symptomatic cutaneous manifestations of advanced cutaneous lymphoma or leukemia, total skin electron beam therapy is an efficient and well tolerated considerable treatment option.